Hubungan Kecemasan Kompetitif Dengan Performa Bertanding Atlet Beladiri Kempo Di Kota Kupang - Pah, Florentia Cindhy Luciana; Berek, Noorce Ch.; Keraf, Abdi (Jurnal Inovasi Global, 2025)
This study aims to determine the relationship between competitive anxiety and performance among kempo martial arts athletes in Kupang City. Competitive anxiety is a psychological condition often experienced by athletes before and during competitions, which can affect the quality of their performance. This research employs a quantitative approach with a survey method. The sample consisted of 274 kempo athletes selected using purposive sampling. Data were collected using two instruments: the Sport Competition Anxiety Test (SCAT) to measure anxiety and a peak performance scale to assess performance. Data analysis results indicate that most athletes fall into the low anxiety and low performance categories. A simple linear regression test revealed a significant negative relationship between competitive anxiety and performance. The higher the athlete’s competitive anxiety level, the lower their performance. These findings highlight the importance of addressing psychological aspects in athlete training, particularly in managing anxiety to achieve optimal performance.